Entre jeu et nostalgie. Les topoï courtois dans Les Trois Aveugles de Compiègne de Jean Ott - Gęsicka, Anna (Romanica Silesiana, 2021)
The subject of this paper is an analysis of Jean Ott’s theater play Les Trois Aveugles de Compiègne. In his adaptation of a 13th-century famed “fabliau” Jean Ott (1878–1935), a lesser-known French author, offers its receiver an interesting intertextual play. In a manner that is both parodic and nostalgic he appeals to the courtly topoi, treating it as a signpost that defines the development of action and the semantic scope of his work.